KADAR HEMOGLOBIN DAN JUMLAH ERITROSIT PUYUH JEPANG (Coturnix coturnix japonica L.) SETELAH PEMBERIAN TEPUNG KUNYIT (Curcuma longa L.) DAN TEPUNG IKAN DALAM PAKAN - Panji Setiawan (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2017)
This study aims to examine the effect of turmeric powder and fish meal administration after the productivity declining period on hemoglobin level and total erythrocyte of japan quail (Coturnix coturnix japonica L.). This study use the Completely Randomized Design (CRD) and analyzed with ANOVA followed by a Duncan test. Sixty quails were divided into four groups, each consist of three quails with five replications. the study concludes on the ninth month. The treatments were AP0: Quails were given standard feed, AP1: Quails were given standard feed and turmeric 54mg / quail / day on 7-8 months old, BP0: Quails were given standard feed plus 85% fish meal, 15 %, BP1: Quails were given feed standard 85%, 15% fish meal, and and turmeric powder 54mg/ quail /day on 7-8 months old. The results of this study showed that administration of turmeric powder in the feed affected hemoglobin level and total erythrocyte. Addition of turmeric powder in the feed can repair blood metabolism japan quail (Coturnix coturnix japonica L.). While, fish meal in the feed did not affect hemoglobin level and total erythrocyte the japan quail (Coturnix coturnix japonica L.).Keywords: Fish Meal, Hemoglobin level, Japan Quail (Coturnix coturnix japonica L.), Total Erythrocyte, and Turmeric